Advancements in distributed computing and Internet technologies: trends and issues - Pathan, Al-Sakib Khan (IGI Global, 2011)
Advancements in Distributed Computing and Internet Technologies: Trends and Issues compiles recent research trends and practical issues in the fields of distributed computing and Internet technologies. The book provides advancements on emerging technologies that aim to support the effective design and implementation of service-oriented networks, future Internet environments, and building management frameworks. Research on Internet-based systems design, wireless sensor networks and their application, and next generation distributed systems will inform graduate students, researchers, academics, and industry practitioners of new trends and vital research in this evolving discipline.